2017
DOI: 10.1007/s00167-017-4772-7
|View full text |Cite
|
Sign up to set email alerts
|

Medial stabilized and posterior stabilized TKA affect patellofemoral kinematics and retropatellar pressure distribution differently

Abstract: Patellofemoral kinematics and retropatellar pressure change after TKA in different manner depending on the type of TKA used. Surgeons should be aware of influencing the risks of patellofermoral complications by the choice of the prosthesis design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Although some previous studies showed no significant differences between AFO restoration and clinical outcomes, there was a trend towards improved outcomes [ 3 , 45 ]. Other studies showed that if the AFO increased after TKA and there was a risk of overstuffing due to the mismatch of the prosthesis, the pressure of the patellofemoral joint would increase, and then, there would be complications such as anterior knee pain and decreased knee motion [ 46 ]. Taking these issues into account, an increasing number of studies have analysed the shape and variance of the distal femur.…”
Section: Discussionmentioning
confidence: 99%
“…Although some previous studies showed no significant differences between AFO restoration and clinical outcomes, there was a trend towards improved outcomes [ 3 , 45 ]. Other studies showed that if the AFO increased after TKA and there was a risk of overstuffing due to the mismatch of the prosthesis, the pressure of the patellofemoral joint would increase, and then, there would be complications such as anterior knee pain and decreased knee motion [ 46 ]. Taking these issues into account, an increasing number of studies have analysed the shape and variance of the distal femur.…”
Section: Discussionmentioning
confidence: 99%
“…This could affect the external validity of the study, but only in countries where resurfacing is done more or less by default for reasons stated earlier [ 14 , 18 , 33 ]. One study recently implied that postoperative retropatellar pressure is low in medial pivot implants [ 17 ], yet our study showed there is an increased risk for revision due to patellar erosion.…”
Section: Discussionmentioning
confidence: 52%
“…However, we documented a near fivefold risk of revision for malalignment, and a doubled risk of revision for instability in Australia for medial pivot designs compared with cruciate-retaining implants. Some reports indicate that medial pivot design improve patellofemoral biomechanics [ 1 , 17 , 42 ], possibly due to the lack of medial translation and the lateral femoral rollback [ 39 ]. However, other studies fail to report this [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although some previous studies showed no signi cant differences between restoration of AFO and clinical outcomes, there was a trend toward improved outcomes [34,42]. Other studies showed that if the AFO increased after TKA and the there was a risk of overstu ng due to the mismatch of the prosthesis, the pressure of the patellofemoral joint would increase, and then there would be complications such as anterior knee pain and decreased knee motion [20]. If there was a risk of notching of the patellofemoral joint, it leaded to cause instability in knee exion [6].…”
Section: Discussionmentioning
confidence: 95%